PENGARUH MODEL PEMBELAJARAN TANDUR TERHADAP AKTIVITAS DAN HASIL BELAJAR PADA MATERI VIRUS SISWA KELAS X SMA NEGERI 2 SKANTO KABUPATEN KEEROM - Siti Daryati (Jurnal Ilmu Pendidikan Indonesia, 2018)
Abstrack The data analysis using SPSS version 21. Results of regression model of learningTANDUR (X) on learning activities (Y1) with the equation Y1 = 12,977 + 1,662X, the effect of 77.2% and a learning model TANDUR (X) on learning outcomes (Y2 ) with the equation Y2 = -13,399 + 2,283X, the impact of 90,6%. The results of correlation analysis TANDUR learning model (X) on learning activities (Y1) of 0,850 and a learning model TANDUR (X) on learning outcomes (Y2) amounted to 0,952, this means learning model TANDUR effect on activity and learning outcomes.Research results to direct that: (1) there are significant learning model TANDUR on learning activities amounted to 77,2%, (2) there are significant learning model TANDUR the learning outcomes of 90,6%, and (3) there is an increase learning outcomes with value n- average gain of 0,63 learning outcomes with the medium category.Keywords: Learning Model TANDUR, Activities, Learning Outcomes, Virus.